Glass Fracture Upon Ballistic Impact: New Insights From Peridynamics Simulations - Rivera, Jared; Berjikian, Jonathan; Ravinder, R.; Kodamana, Hariprasad; Das, Sumanta; Bhatnagar, Naresh; Bauchy, Mathieu; Krishnan, N. M. Anoop (Frontiers in Materials, 2019)
Most glasses are often exposed to impact loading during their service life, which may lead to the failure of the structure. While in situ experimental studies on impact-induced damage are challenging due to the short timescales involved, continuum-based computational studies are complicated by the discontinuity in the displacement field arising from the propagation of cracks. Here, using peridynamics simulations, we investigate the role of the mechanical properties and geometry in determining the overall damage on a glass plate subjected to ballistic impact. In particular, we analyze the role of bullet velocity, bullet material, and elastic modulus, fracture energy, and radius of the plate. Interestingly, we observe a power-law dependence between the total damage and the fracture energy of the glass plate. Through an auto-regressive analysis of the evolution of cracks, we demonstrate that the self-affine growth of cracks leads to this power-law dependence. Overall, the present study illustrates how peridynamics simulations can offer new insights into the fracture mechanics of glasses subjected to ballistic impacts. This improved understanding can pave way to the design and development of glasses with improved impact-resistance for applications ranging from wind-shields and smart-phone screens to ballistics.